Gamma Ray Showers Observed at Ground Level in Coincidence With Downward Lightning Leaders. Issue 13 (2nd July 2018) - Abbasi, R. U.; Abu‐Zayyad, T.; Allen, M.; Barcikowski, E.; Belz, J. W.; Bergman, D. R.; Blake, S. A.; Byrne, M.; Cady, R.; Cheon, B.G.; Chiba, J.; Chikawa, M.; et al.
Abstract: Bursts of gamma ray showers have been observed in coincidence with downward propagating negative leaders in lightning flashes by the Telescope Array Surface Detector (TASD). The TASD is a 700‐km 2 cosmic ray observatory located in southwestern Utah, USA. In data collected between 2014 and 2016, correlated observations showing the structure and temporal development of three shower‐producing flashes were obtained with a 3‐D lightning mapping array, and electric field change measurements were obtained for an additional seven flashes, in both cases colocated with the TASD. National Lightning Detection Network information was also used throughout. The showers arrived in a sequence of 2–5 short‐duration (≤10  μ s) bursts over time intervals of several hundred microseconds and originated at an altitude of ≃3–5 km above ground level during the first 1–2 ms of downward negative leader breakdown at the beginning of cloud‐to‐ground lightning flashes. The shower footprints, associated waveforms and the effect of atmospheric propagation indicate that the showers consist primarily of downward‐beamed gamma radiation. This has been supported by GEANT simulation studies, which indicate primary source fluxes of ≃10 12 –10 14 photons for 16° half‐angle beams. We conclude that the showers are terrestrial gamma ray flashes, similar to those observed by satellites, but that the ground‐based observations are more representative of the temporal source activity and are also more sensitive than satellite observations, which detect only the most powerful terrestrial gamma ray flashes. Key Points: Gamma ray showers have been detected in a surface scintillator array coincident with lightning observed by a lightning mapping array or Delta E antenna The showers were produced less than 4–5 km above ground in the first 1–2 ms of downward negative breakdown during cloud‐to‐ground flashes The source durations are better resolved than for satellite observations and are consistent with being produced by stepping of the initial leader breakdown